Pengaruh Kepemimpinan Dan Kompensasi Terhadap Kepuasan Kerja Karyawan Outsourcing Pada PT. BRI (Persero), tbk. Cabang Lumajang - Muttaqien, Fauzan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2014)
Influence of Leadership and Compensation Employee Satisfaction Against Outsourcing at. BRI (Persero),Tbk. Branch Lumajang conducted by survey (eskplanatory analytical , with a sample of 42 employees of outsourcing and using correlation and regression analysis). Operationally purpose of this study is to investigate and test empirically (1) Effect of simultaneous compensation of leadership and employee job satisfaction outsourcing, (2) Effect of partial compensation of leadership and employee job satisfaction outsourcing, (3) Which of the dominant independent variable influence on employee job satisfaction outsourcing. Results show the following: 1 ) The first hypothesis is that the testing simulatan influence of leadership on job satisfaction and compensation amounting to 20.305 and Fcount known Ftable 3,232 , because of Fcount > F table the first hypothesis can be accepted . 2 ) For the second hypothesis about the partial effect of leadership on job satisfaction and compensation known result that tcount Leadership and Compensation for 2042 amounted to 4,630 compared with the known ttable 2,021 so tcount > ttable thus the second hypothesis can be accepted. 3 ) As shown by the standardized coefficient B, variable compensation = 0.571 greater than 0.252 leadership variables. Thus it is said that the variable compensation has a dominant influence on job satisfaction.